The Roman Catholic View of Sunday: A Theological Evaluation - Koberson Langhu (Fakultas Filsafat Universitas Advent Indonesia, 2023)
The Christian faith arose from a Jewish cultural and religious background. The earliest Christians were Jews who observed the various Jewish religious practices including the Saturday Sabbath. In the early centuries, many Gentiles converted to Christianity. With the persecution of the Christians by the Jews and the Romans, the Christians distanced themselves from the Jews. They rejected many of the Jewish customs and practices including the Sabbath. In the early centuries, the change from the Sabbath to Sunday was made. Since then, Christianity has been divided doctrinally on the Sabbath and Sunday issue. The Roman Catholic Church played significant role in the origin and observance of Sunday. This paper is an attempt to understand the teachings of the Catholic Church on the Sabbath and Sunday. The study reveals that the Church bases its teachings on the subject on different biblical hermeneutics supported by Church Tradition. The Church argues for a replacement theology for the Jewish Sabbath on the ground of the resurrection of Christ. It also claims to have made the change from the Sabbath to Sunday on divine prerogatives and authority vested in the Church by God.